2015
DOI: 10.1093/mnras/stv1042
|View full text |Cite
|
Sign up to set email alerts
|

Surface photometry of brightest cluster galaxies and intracluster stars in ΛCDM

Abstract: We simulate the phase-space distribution of stellar mass in nine massive ΛCDM galaxy clusters by applying the semi-analytic particle tagging method of Cooper et al. to the Phoenix suite of high-resolution N -body simulations (M 200 ≈ 7.5-33 × 10 14 M ). The resulting surface brightness (SB) profiles of brightest cluster galaxies (BCGs) match well to observations. On average, stars formed in galaxies accreted by the BCG account for 90 per cent of its total mass (the remainder is formed in situ). In circular BCG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
146
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(168 citation statements)
references
References 127 publications
(232 reference statements)
22
146
0
Order By: Relevance
“…They suggested that their blue GCs at distances >215 kpc are part of the intracluster component of Virgo. Cosmological simulations Cui et al 2014;Cooper et al 2015) predict that the density of this component would then increase inwards. Durrell et al (2014) also found evidence for a spatial asymmetry of GCs surrounding M 87 for major axis distances larger than 20 , with an excess of tracers in the NW region (mostly the blue population).…”
Section: Is There An Intracluster Component Of Gcs Around M 87?mentioning
confidence: 99%
See 3 more Smart Citations
“…They suggested that their blue GCs at distances >215 kpc are part of the intracluster component of Virgo. Cosmological simulations Cui et al 2014;Cooper et al 2015) predict that the density of this component would then increase inwards. Durrell et al (2014) also found evidence for a spatial asymmetry of GCs surrounding M 87 for major axis distances larger than 20 , with an excess of tracers in the NW region (mostly the blue population).…”
Section: Is There An Intracluster Component Of Gcs Around M 87?mentioning
confidence: 99%
“…Using a particle tagging method to analyse galaxy clusters in ΛCDM simulations, Cooper et al (2015) consider the BCG and ICL as a single entity consisting of all stars, which are not bound to any cluster subhalos. They then split the BCG stars into accreted stars and in situ stars, and find that the large majority of BCG stars are accreted stars.…”
Section: Relation Between Bcg and Iclmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that the overall structure of stellar halos, their stellar populations, and the properties of their dynamical substructures directly probe two fundamental aspects of galaxy formation in the ΛCDM (cold dark matter) model: the hierarchical assembly of massive galaxies and their dark matter halos and the balance between in situ star formation and the accretion of stars through mergers (Cooper et al 2013(Cooper et al , 2015a(Cooper et al , 2015bPillepich et al 2015).…”
Section: Introductionmentioning
confidence: 99%